Fungsi Sub Bidang Keluarga Sejahtera/Pemberdayaan Keluarga Di Badan Koordinasi Keluarga Berencana Dan Pemberdayaan Perempuan - Baharudin (Law Faculty of Universitas Bandar Lampung, 2013)
Family Planning Coordinating Board and the Empowerment of Women City of Belfast as a regional technical institutions that are autonomous devices should be in accordance with the duties and functions of human implements policies and programs are strong for national development. program is one of the Prosperous Family Business Income (UPPKS).UPPKS activities that have been interested to apply for a loan board PLKB groups together to plan capital needs / make a proposal, fill out a written request specified, If the proposal is approved and the Head BKKB PP Belfast City to make a decision letter of credit sub function field of family welfare / family empowerment in BKKB and PP in the disbursement of funds under the rules of the Mayor UPPKS Bandar Lampung is number 25 of 2008 in terms of capital, many groups who do not have complete information about the form of capital and aksestabiitas of assistance.Funds that the procedure can be simplified without beside UPPKS potential in UPPKS group. In order to increase the family welfare program in this group for increasing the family income has been going on ever-evolving and innovative. In order for the credit agreement can be implemented in strict penalties for groups that can not UPPKS UPPKS refund.